Analisa dan Perancangan Tata Kelola Akses Internet Gratis pada Café Roose Menggunakan Mikrotik Rb 750 - Ari Syaripudin (Jurnal Informatika Universitas Pamulang, 2018)
Free internet access provided at a café is expected to increase the interest of café visitors. Cafe Roose provides free internet access to consumers, it is expected that with free internet access, the number of visitors to the café will increase. Free internet access is spread through WIFI devices that use a 2.4 Ghz frequency. This wifi is used because almost all communication devices are used such as Smart Phones and laptops using WIFI. The problem that arises is that internet access on public networks requires high protection so as not to be misused, the increasing number of users causes the internet access to be unstable. Officers also cannot control the use of internet access. From these problems, the governance of free internet access was made on roose café using mikrotik rb 750.